2006
DOI: 10.1037/0893-3200.20.2.266
|View full text |Cite
|
Sign up to set email alerts
|

Effects of attachment-based interventions on maternal sensitivity and infant attachment: Differential susceptibility of highly reactive infants.

Abstract: The current intervention study aimed at breaking the potential intergenerational cycle of insecure attachment. The authors randomly assigned 81 first-time mothers to one of two intervention groups or a control group. The interventions involved four home visits when the infants were between 7 and 10 months old. The first intervention, VIPP, consisted of video-feedback and brochures to enhance sensitive parenting. The second intervention, VIPP-R, involved additional discussions of mothers' childhood attachment e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
181
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 244 publications
(196 citation statements)
references
References 36 publications
12
181
0
3
Order By: Relevance
“…The use of the ICQ (Bates et al, 1979) to assess temperament limits the temperamental dimension included in the current intervention to difficultness. Other dimensions may be more important from the perspective of differential susceptibility, such as behavioral inhibition (Kagan, Reznick, & Gibbons, 1989), fearfulness (Kochanska, 1995), or emotional reactivity (Belsky, 2005;Klein Velderman et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of the ICQ (Bates et al, 1979) to assess temperament limits the temperamental dimension included in the current intervention to difficultness. Other dimensions may be more important from the perspective of differential susceptibility, such as behavioral inhibition (Kagan, Reznick, & Gibbons, 1989), fearfulness (Kochanska, 1995), or emotional reactivity (Belsky, 2005;Klein Velderman et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…To test whether children with a difficult temperament were more susceptible to the intervention efforts than relatively easy children, we split the sample into a group of temperamentally difficult children and a group of children with a relatively easy temperament. An a priori split was made on the 82.7th percentile in the general population screening sample, in accordance with the commonly used borderline/clinical cutoff for the CBCL (see also Klein Velderman et al, 2006). Because the three age groups differed in their temperament levels, splits were made separately for each age group.…”
Section: Instrumentsmentioning
confidence: 99%
“…16 Furthermore, genetic differential susceptibility theory, which has been put forward by BakermansKranenburg and van IJzendoorn, 17 specifically emphasizes the moderating role of genetic variance that act as plasticity markers in gene 3 environment paradigms. 18 A significant proportion of the differential susceptibility literature has focused on a common variation in the serotonin transporter gene (5-HTTLPR). 19,20 Two functional alleles, long (L) and short (S), result from a 43-bp insertion/deletion in the promoter region of 5-HTT.…”
Section: Sleep Disturbances In Infants Arementioning
confidence: 99%
“…In a seminal ES experiment, Velderman et al [37] found that infant temperamental reactivity, a putative ES factor, moderated outcomes of a brief-type preventive intervention aimed at improving maternal sensitivity and attachment security. Specifically, the intervention was most effective for mothers with highly reactive infants; on the other hand, for mothers with low reactive infants, there was no association between gains in maternal sensitivity and attachment security.…”
Section: Experimental Evidence Of Esmentioning
confidence: 99%